2019
DOI: 10.7567/1882-0786/ab31b9
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared Er:CaF2–SrF2 bulk laser Q-switched by MXene Ti3C2T x absorber

Abstract: We report a diode-pumped passively Q-switched Er:CaF2–SrF2 laser at 2.73 μm with MXene Ti3C2Tx as a saturable absorber (SA). A maximum average output power of the pulsed laser was measured at 286 mW, with a shortest duration of 814 ns and a repetition rate of 45.3 kHz. The corresponding single-pulse energy and peak power were calculated to be 6.32 μJ and 7.76 W, respectively. The results suggest the promising potential of MXene as an efficient SA for short pulse lasers in the mid-infrared spectral band.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Due to the operating bandwidth of the TBPF, the Qswitching range was limited to between 1895 nm to 2050 nm. However, Feng et al (2018) [55], Wang et al (2018) [56] and Hao et al (2019) [57] had previously demonstrated Q-switched outputs at 1064 nm, 1300 nm, and 2730 nm using MXene based SAs. As such, it is quite likely that Q-switching beyond 1895 nm to 2050 nm can also be achieved from the proposed cavity of this work through the use of a TBPF with a wider pass-through bandwidth.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the operating bandwidth of the TBPF, the Qswitching range was limited to between 1895 nm to 2050 nm. However, Feng et al (2018) [55], Wang et al (2018) [56] and Hao et al (2019) [57] had previously demonstrated Q-switched outputs at 1064 nm, 1300 nm, and 2730 nm using MXene based SAs. As such, it is quite likely that Q-switching beyond 1895 nm to 2050 nm can also be achieved from the proposed cavity of this work through the use of a TBPF with a wider pass-through bandwidth.…”
Section: Resultsmentioning
confidence: 99%
“…The MXenes SAs demonstrated the highest average output power of 150 mw when compared to other visible Qswitching lasers based on low-dimensional SAs. A variety of gain mediums were employed to obtain different wavelength outputs of Ti 3 C 2 T x SAM Q-switching laser, which include Nd:YAG, [147] YVO 4 /Nd:YVO 4 /YVO 4 , [149] Ho,Pr:LLF, [150] Er:CaF 2 -SrF 2, [152] Pr: LiYF 4, [155] Er: ZBLAN, [161] Ho: YLF, [157] and Gd:CaF 2 . [158] These gain mediums provide a broad operating wavelength range of 600-3000 nm with Ti 3 C 2 T x SAM Q-switching laser.…”
Section: Q-switching Lasermentioning
confidence: 99%
“…However, the majority of existing reports on Ti 3 C 2 T x twodimensional film used as a SA in passively Q-switched lasers focus on wavelengths at 1.06 µm, 1.3 µm, 2.73 µm, and 3 µm. [16][17][18][19] Few of the reports are about Ti 3 C 2 T x used as an SA for passively Q-switched lasers at 1123 nm.…”
Section: Introductionmentioning
confidence: 99%